La Villa Imperiale di Punta Eolo rivestimenti Pavimentali e parietali del settore residenziale - De Vos, Mariette 1944-; Maurina, Barbara (Archaeopress, 2023)
The Roman villa of Punta Eolo is a large 'pavilion villa' on the northern promontory of the island of Ventotene. A large number of fragmentary frescoes, stuccoes, pavement revetments and Campana reliefs were brought to light in the residential area of the Villa during the archaeological excavations by G.M. De Rossi in the years 1990-2005.
Keywords: Villa; Römerzeit; Ventotene